Sleep quality patterns in patients with heart failure: a person-centred latent class analysis from a secondary analysis of the MOTIVATE-HF trial - Ercole Vellone; Laura Rasero; Barbara Riegel; Rosaria Alvaro; Paolo Iovino; Hamilton Dollaku; Gianluca Pucciarelli; Claudio Macchi; Piergiuseppe Liuzzi (BMJ Open)
Objectives To identify distinct sleep quality patterns among patients with heart failure (HF) using a person-centred approach and explore demographic and clinical predictors of these patterns.Design Secondary analysis of baseline cross-sectional data from the MOTIVATE-HF (MOTIVATional intErviewing to improve self-care in Heart Failure patients) randomised controlled trial. Latent class analysis (LCA) was applied to Pittsburgh Sleep Quality Index (PSQI) component scores to identify distinct subgroups of patients. Demographic, clinical and psychological variables were examined as potential predictors of cluster membership.Setting Three healthcare settings in Italy: hospital, outpatient and community-based care.Participants 510 adult patients diagnosed with HF (New York Heart Association (NYHA) class II–IV) with poor self-care were included. Patients with severe cognitive impairment or recent myocardial infarction were excluded.Primary and secondary outcome measures Primary outcome: Sleep quality, measured using the PSQI, analysed through LCA to identify sleep disturbance clusters. Secondary outcomes included demographic and clinical characteristics predicting cluster membership.Results The mean age was 72.4 years (SD=12.3), with most participants married or partnered (62%) and retired or unemployed (83.9%). Mild comorbidities were present in 53.3% of the sample (mean Charlson Comorbidity Index (CCI)=2.91, SD=1.98), and 61.4% were classified in NYHA class II. Three sleep quality clusters emerged: (1) adequate sleep duration but disturbed sleep and daytime dysfunction (46.1%); (2) severe sleep problems with low use of sleeping medications (25.3%); and (3) minor sleep problems with mild disturbances (28.6%). Patients in Cluster 1 were older (mean age=73.3 years), had lower physical and mental quality of life (Short-Form 12 Physical Component Summary=33.66; Mental Component Summary=42.65), and higher anxiety (Hospital Anxiety and Depression Scale-A=8.82). Patients in Cluster 2 had more severe comorbidities (CCI=3.55), poorer cognitive function (Montreal Cognitive Assessment (MoCA)=21.5) and lower ejection fraction (mean=40%). Patients in Cluster 3 were younger (mean age=68.2 years), had better cardiac function (ejection fraction=46.6%), better cognitive status (MoCA=24.5) and the highest quality of life (Kansas City Cardiomyopathy Questionnaire=63.1).Conclusions Patients with HF exhibit heterogeneous sleep quality patterns with specific clinical and psychological profiles. These findings highlight the need for personalised interventions, systematic sleep assessments and the integration of cardiac rehabilitation strategies into standard HF care.Trial registration number NCT02894502.